2004
DOI: 10.5380/fsd.v6i1.8075
|View full text |Cite
|
Sign up to set email alerts
|

Alimentação De Crianças De 3 a 6 Anos Que Frequentam Instituições De Educação Infantil, Segundo Suas Mães

Abstract: RESUMO: Objetivo -conhecer as percepções de mães sobre a alimentação de seus filhos de três a sete anos incompletos que freqüentam instituições de educação infantil. Metodologia -a pesquisa qualitativa que permite conhecer, interpretar e compreender o fenômeno segundo a ótica dos sujeitos. Usou-se entrevista diretiva individual analisada segundo o conteúdo. Resultados -foram obtidas três categorias: alimentação das crianças em casa, uso de estratégias a fim de estimular a ingesta da criança e melhora do hábito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Issues concerning unhealthy habits and disobeying maternal commands were indicated as problems in the two stages of development. In relation to food, a qualitative study on the perceptions of mothers about the children's diet [13] discusses how mothers are often unaware that some difficulties are common and end up using inappropriate strategies. The survey results indicated that the use of occasional negative interventions continues even after the eating behavior has changed, possibly due to the distress suffered by mothers concerned with their child's diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Issues concerning unhealthy habits and disobeying maternal commands were indicated as problems in the two stages of development. In relation to food, a qualitative study on the perceptions of mothers about the children's diet [13] discusses how mothers are often unaware that some difficulties are common and end up using inappropriate strategies. The survey results indicated that the use of occasional negative interventions continues even after the eating behavior has changed, possibly due to the distress suffered by mothers concerned with their child's diet.…”
Section: Discussionmentioning
confidence: 99%
“…One characteristic of this phase concerning parents refers to the child's diet. It is common in this period that children present food neophobia; however, parents often worry that their child is not eating properly, and end by using inappropriate feeding strategies [13]. Another problem refers to the gastroesophageal reflux disease, which is significantly related to feeding problems and oral disorders [14].…”
Section: Introductionmentioning
confidence: 99%